2017
DOI: 10.1002/etc.3881
|View full text |Cite
|
Sign up to set email alerts
|

Size‐ and shape‐dependent effects of microplastic particles on adult daggerblade grass shrimp (Palaemonetes pugio)

Abstract: The incidence of microplastics in marine environments has been increasing over the past several decades. The objective of the present study was to characterize the size- and shape-dependent effects of microplastic particles (spheres, fibers, and fragments) on the adult daggerblade grass shrimp (Palaemonetes pugio). Grass shrimp were exposed to 11 sizes of plastic: spheres (30, 35, 59, 75, 83, 116, and 165 μm), fragments (34 and 93 μm), and fibers (34 and 93 μm) at a concentration of 2000 particles/400 mL (= 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
156
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 346 publications
(180 citation statements)
references
References 35 publications
(56 reference statements)
7
156
3
Order By: Relevance
“…As a result, grass shrimp were able to depurate the majority of ingested particles during the 48‐h period in particle‐free water (Figure ). These results are consistent with those of Gray and Weinstein (), who determined that the average residence time for microplastics in the digestive tract and gills of grass shrimp was 43.0 ± 13.8 and 36.9 ± 5.4 h, respectively. The ability of grass shrimp to depurate these particles likely limited the physical toxicity of the particles (Wright et al ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…As a result, grass shrimp were able to depurate the majority of ingested particles during the 48‐h period in particle‐free water (Figure ). These results are consistent with those of Gray and Weinstein (), who determined that the average residence time for microplastics in the digestive tract and gills of grass shrimp was 43.0 ± 13.8 and 36.9 ± 5.4 h, respectively. The ability of grass shrimp to depurate these particles likely limited the physical toxicity of the particles (Wright et al ).…”
Section: Discussionsupporting
confidence: 93%
“…Despite the absence of mortalities or immunotoxicity in the present 96‐h exposure study, the number of particles present in the shrimp gut ranged from 0 to 208 particles/individual (Figure ) and in the gills ranged from 0 to 5 particles/individual (Figure ). In contrast, Gray and Weinstein () reported much lower uptake of particles in the gut and gills of grass shrimp following a 3‐h, 50 000 particles/L exposure to polyethylene spheres, polystyrene spheres, polypropylene fragments, or weathered polypropylene fibers in the same size range used for our study, but nonetheless documented mortalities from the microplastic exposure. These results highlight the variability in the number of ingested and ventilated particles/shrimp and suggest that the accumulation of particles in the gut of grass shrimp increases with exposure time.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…A study of Northern Fulmar seabirds off the coast of Norway showed that levels of hazardous organic pollutants in the birds had no correlation to the amount of plastic in their stomachs (Burton ). Another study by Gray and Weinstein () showed that the toxicity depended on the size and shape of microplastics. Spheres and fragments smaller than 50 μm had no acute effects but were acutely toxic at larger sizes, as were fibers at 93 μm (Burton ).…”
Section: Toxicitymentioning
confidence: 99%